Stellar astrophysical fluid dynamics - Thompson, M. J. (Michael J.); Christensen-Dalsgaard, Jørgen, 1950- (Cambridge University Press, 2003)
A comprehensive overview of the current state of knowledge in stellar astrophysical fluid dynamics. Topics include properties of pulsating stars, helioseismology, convection and mixing in stellar interiors, dynamics of stellar rotation, planet formation and the generation of stellar and planetary magnetic fields.